2007
DOI: 10.1371/journal.pone.0000443
|View full text |Cite
|
Sign up to set email alerts
|

Order in Spontaneous Behavior

Abstract: Brains are usually described as input/output systems: they transform sensory input into motor output. However, the motor output of brains (behavior) is notoriously variable, even under identical sensory conditions. The question of whether this behavioral variability merely reflects residual deviations due to extrinsic random noise in such otherwise deterministic systems or an intrinsic, adaptive indeterminacy trait is central for the basic understanding of brain function. Instead of random noise, we find a fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
198
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(219 citation statements)
references
References 92 publications
19
198
0
2
Order By: Relevance
“…(similar to our shorter experiments here) has shown that, during extended flights, the occurrence of turning maneuvers can be described by a Lévi distribution (Maye et al, 2007). Such distributions of behavioral output, seen in foraging behavior in many animals, are characteristically long-tailed.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…(similar to our shorter experiments here) has shown that, during extended flights, the occurrence of turning maneuvers can be described by a Lévi distribution (Maye et al, 2007). Such distributions of behavioral output, seen in foraging behavior in many animals, are characteristically long-tailed.…”
Section: Discussionsupporting
confidence: 85%
“…Flies were tethered as described previously (Maye et al, 2007) and tested the following day for flight behavior (for a video of the procedure, see Brembs, 2008). The duration of the experiments had to be confined to 6 min because radish mutants were reluctant to fly continuously in the arena.…”
Section: Methodsmentioning
confidence: 99%
“…Under such conditions, an innate movement process could account for the movement patterns we observed in albatrosses, and could apply more generally. Although there is no clear evidence of an innate Lévy process driving movements of vertebrates, experimental studies have shown that in featureless environments Drosophila activity patterns are well approximated by a Lévy flight (8,27). Furthermore, Drosophila with silenced parts of the brain's mushroom body, or modified dopaminergic signaling-circuitry linked to decision-making-show disrupted activity patterning and behavioral burstiness, where burstiness is described as heavy-tailed distributions of move or pause times (28).…”
Section: Resultsmentioning
confidence: 99%
“…In saltatory searches, where scanning is discontinuous, reorientation behavior might be linked to decision-making mechanisms capable of stopping and/or starting relocation moves in different directions. In both cases, the mechanisms themselves could consist of simple internal biological programs (6,43) or could emerge as interactive processes with other individuals (i.e., collective mechanisms of intermittence) or the environment (i.e., relocation displacements). As occurs in dispersal processes, for example, many animals could actively take benefit of external transportation devices (e.g., winds, ocean currents, other animals) as part of a search strategy.…”
Section: Discussionmentioning
confidence: 99%
“…There are some examples in the literature showing that at least for ''simple'' organisms (e.g., bacteria, flagellates, fruit flies) motor-related neuronal configurations (43,44) and biochemical paths (45) could be responsible for a Lévy timing of reorientations (12,13,44,46). Empirical evidence of such fractal reorientation clocks at different levels of biological organization (e.g., neuronal, biochemical, physiological, behavioral) could explain, to some extent, the presence of Lévy flights and scale-free (i.e., fractal) properties in the movement patterns of some animals (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%